Research on the decoupling relationship between water resources utilization and economic development at the county scale in Qian’nan Prefecture, Guizhou Province - Su, Yin; Liao, Shenghai; Ren, Jintong; Zhao, Zulun (Frontiers in Environmental Science, 2024)
To understand the relationship between water resources and economic development in Qian'nan, Guizhou, the water resources ecological footprint and decoupling model were used to analyze the dynamic change characteristics and spatial distribution characteristics of the water resources ecological footprint of different water accounts in Qian'nan. The relationship between water resource ecological footprint and economic growth was analyzed. The results show that: from 2009 to 2019, the ecological footprint of water resources in Qian'nan is less than the ecological carrying capacity of water resources. The water resources are in a state of surplus, the ecological pressure is small, and the utilization rate of water resources is gradually increasing; The ecological footprint of water resources is higher in the north than in the south. Areas with high economic levels have large ecological footprints of water resources, while areas with low economic levels have small ecological footprints of water resources; Apart from a few counties (cities) where the relationship between water resource ecological footprint and economic growth is increasingly severe, the overall relationship between water resources ecological footprint and economic growth in other counties (cities) is in a state of weak decoupling, indicating that economic development is not constrained by water resources.